Ph3P-I2 mediated aryl esterification with a mechanistic insight - Phakhodee W. (2017)
© 2016 Elsevier Ltd. All rights reserved. In order to better understand the reaction mechanism and to obtain optimal conditions, the Ph 3 P-I 2 /Et 3 N mediated aryl esterification reaction was thoroughly investigated. Using a specific reagent addition sequence, the reaction proceeds remarkably well especially with acidic substrates. 31 P NMR studies revealed that the formation of an aryloxyphosphonium salt is crucial in governing the reaction path toward the formation of phenolic esters.